2019
DOI: 10.1145/3359141
|View full text |Cite
|
Sign up to set email alerts
|

How Data Scientists Use Computational Notebooks for Real-Time Collaboration

Abstract: Effective collaboration in data science can leverage domain expertise from each team member and thus improve the quality and efficiency of the work. Computational notebooks give data scientists a convenient interactive solution for sharing and keeping track of the data exploration process through a combination of code, narrative text, visualizations, and other rich media. In this paper, we report how synchronous editing in computational notebooks changes the way data scientists work together compared to workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 25 publications
1
74
0
Order By: Relevance
“…Computational notebooks are positioned as a potential solution to both support collaborative coding and communicating results to stakeholders [78]. However, a recent study reported reluctance for data scientists to directly communicate the in-progress model work in notebooks [65].…”
Section: Data Science Practices and Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational notebooks are positioned as a potential solution to both support collaborative coding and communicating results to stakeholders [78]. However, a recent study reported reluctance for data scientists to directly communicate the in-progress model work in notebooks [65].…”
Section: Data Science Practices and Collaborationmentioning
confidence: 99%
“…For P2, domain experts gave an overview and touched on the basic concepts of each class. P3 pair-authored [78] with domain experts to bridge concepts and a mathematical formula that encapsulates the information. With this iterative learning process, data scientists were able to kick start model building.…”
Section: Limited Time and Limited Best Practicesmentioning
confidence: 99%
“…These jumps cause changes in context, both in terms of the program state and analysts' mental models. The challenge of managing segments of analysis state is also faced in collaboration settings, where analysts sometimes jump through cells and need to understand cell dependencies [55]. Supporting analysts in navigating between segments of analysis in space and time poses additional challenges for the layout and temporal gaps.…”
Section: Non-linear Workflows and Asynchronous Collaborationsmentioning
confidence: 99%
“…The challenge is that this process is labor intensive, requiring input from multiple specialists with different skill sets [1,31,34,47,48]. As a result, AI and Human-Computer Interaction (HCI) researchers have investigated how to design systems with features that support data scientists in creating machine learning models [24,28,34,41,42,44]. This Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%
“…Kross & Guo users expressed a strong desire for an integrated user interface with both code and narrative. These needs are perhaps best captured in the narrative uses [24] of the Jupyter Notebook environment [20,21], and researchers have conducted numerous studies of how data scientists incorporate notebooks into their workflows [38,41], how they conduct version control for notebooks [23], and how they enable simultaneous multi-user editing in notebooks [42].…”
Section: Introductionmentioning
confidence: 99%